Schiff base corrosion inhibitor as well as preparation method and application thereof

Through the aldehydeamine condensation polymerization reaction of para-phenylenediamine and terephthalaldehyde, Schiff alkali corrosion inhibitor with planar structure was prepared, which solved the problems of complex and high cost in the prior art, and achieved efficient and environmentally friendly corrosion inhibition effect of carbon steel.

CN119684547APending Publication Date: 2025-03-25SHANGHAI UNIVERSITY OF ELECTRIC POWER
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411595122.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-11
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

The existing Schiff alkali corrosion inhibitor synthesis process is complex and has high cost. It requires the addition of catalyst and water removal agent. The amount added during use is large, which affects environmental protection and economicality.

Method used

By conducting aldehydeamine condensation polymerization reaction in N,N-dimethylformamide with a planar structure, Schiff alkali corrosion inhibitor is prepared, with a polymerization degree of 20-50 and a molecular weight of 3500-9000. The process is simple, there are few side reactions and high yields.

Benefits of technology

The obtained Schiff alkali corrosion inhibitor has excellent corrosion inhibition effect on carbon steel in 1mol·L-1HCl solution, with a corrosion inhibition rate of up to 90.04%, and shows a significant corrosion inhibition effect at a lower concentration, and is environmentally friendly in the process, cost-effective and efficient.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119684547A_ABST
    Figure CN119684547A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of corrosion inhibitors, and relates to a Schiff base corrosion inhibitor as well as a preparation method and application thereof. According to the invention, p-phenylenediamine and terephthalaldehyde are dissolved in N, N-dimethylformamide for an aldehyde-amine condensation polymerization reaction to generate a Schiff base corrosion inhibitor with a plane structure, so that the interaction with the surface of carbon steel is enhanced. Compared with the prior art, the preparation method disclosed by the invention is simple, few in side reaction and high in yield, and the obtained Schiff base corrosion inhibitor has an excellent corrosion inhibition effect on carbon steel in a 1 mol.L <-1 > HCl solution.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of corrosion inhibitors, and in particular relates to a Schiff base corrosion inhibitor and a preparation method and application thereof. Background Art

[0002] Corrosion inhibitors are commonly used to slow down metal corrosion, with the advantages of low cost, simplicity, convenience and significant effect. Among the known types of corrosion inhibitors, organic matter, especially organic compounds containing a large number of heteroatoms (such as N, S, O, P) and unsaturated π bonds, is still the most effective and cost-effective choice. However, most organic corrosion inhibitors may cause environmental pollution.

[0003] Schiff bases are synthesized through the condensation reaction of aldehydes and amines. Due to the imine (C=N) group in its molecule, Schiff bases show higher corrosion inhibition efficiency than the corresponding aldehydes and amines. Schiff bases are widely used as corrosion inhibitors for carbon steel because of their simple preparation, significant corrosion inhibition effect and good biocompatibility. However, the imine group of Schiff bases with multiple branches will be subject to greater steric hindrance when acting on the surface of carbon steel, which may reduce its corrosion inhibition efficiency for carbon steel. Therefore, designing Schiff bases with planar molecular structures can more effectively improve the corrosion inhibition efficiency. Usually, in order to prepare Schiff bases with planar structures, aromatic aldehydes and aromatic amines containing phenyl or pyridine groups are used as raw materials.

[0004] So far, most of the reported Schiff base corrosion inhibitors contain only one imine group, the molecular conjugated surface formed is small, the effect on the carbon steel surface is not strong enough, the corrosion inhibition efficiency is low, and the required amount of Schiff base corrosion inhibitor is large. However, Schiff base polymers contain multiple imine groups, which can form a larger conjugated surface structure, have a strong effect on the carbon steel surface, high corrosion inhibition efficiency, and require less addition.

[0005] Patent CN113930773B provides a dialdehyde starch Schiff base corrosion inhibitor and its preparation method and application. It uses dialdehyde starch and organic polyamine to undergo an aldehyde-amine condensation reaction under the catalytic action of an organic acid to prepare a green, environmentally friendly and water-soluble polymer corrosion inhibitor, which is suitable for use as a hydrochloric acid corrosion inhibitor in carbon steel, especially for corrosion protection of Q235 low-carbon steel, and still maintains excellent corrosion inhibition performance at 60°C. However, in the process of synthesizing the dialdehyde starch Schiff base corrosion inhibitor in this patent, the process is complex and the cost is high: a catalyst needs to be added and the process is carried out under a nitrogen atmosphere, and the amount of catalyst added in actual use is relatively large. Patent CN113621968B provides a corrosion inhibitor for inhibiting metal corrosion, which is obtained by reacting an organic primary amine and an unsaturated aldehyde at 0-35°C; the organic primary amine includes one or a combination of two or more of dodecylamine, octadecylamine, aniline and p-methoxyaniline; the unsaturated aldehyde includes one or a combination of two or more of acrolein, crotonaldehyde and cinnamaldehyde; the weight average molecular weight of the corrosion inhibitor is 5000-10000, and it has a good corrosion inhibition effect under low concentration and high temperature environment conditions, with low synthesis temperature, less raw materials and no metal addition. The corrosion inhibitor is used to inhibit metal corrosion. However, this patent also has the problems of complex process of synthesizing the corrosion inhibitor, the need to add catalysts and dehydrating agents, and a large amount of addition during use. Summary of the invention

[0006] The purpose of the present invention is to provide a Schiff base corrosion inhibitor and a preparation method and application thereof in order to overcome the problems existing in the above-mentioned prior art. The method has simple process, few side reactions and high yield. The obtained Schiff base corrosion inhibitor has a yield of 1 mol·L - 1 It has excellent corrosion inhibition effect on carbon steel in HCl solution.

[0007] The purpose of the present invention can be achieved by the following technical solutions:

[0008] The present invention provides a Schiff base corrosion inhibitor, which is a polymer with a molecular weight of 3500 to 9000 and a structural formula as follows:

[0009]

[0010] Furthermore, the polymerization degree (n-1) of the Schiff base corrosion inhibitor is 20-50.

[0011] On the other hand, the present invention also provides a method for preparing any of the above-mentioned Schiff base corrosion inhibitors, comprising the following steps: an aldehyde-amine condensation polymerization reaction is carried out between p-phenylenediamine and terephthalaldehyde to obtain the Schiff base corrosion inhibitor.

[0012] Further, p-phenylenediamine and terephthalaldehyde are dissolved in N,N-dimethylformamide to cause an aldehyde-amine condensation polymerization reaction.

[0013] Furthermore, p-phenylenediamine is first dissolved in N,N-dimethylformamide, and after stirring evenly, terephthalaldehyde is dissolved in the mixed solution of p-phenylenediamine and N,N-dimethylformamide, and stirring is continued to fully mix the p-phenylenediamine and terephthalaldehyde to cause an aldehyde-amine condensation polymerization reaction.

[0014] Furthermore, the molar ratio of p-phenylenediamine to terephthalaldehyde is 1:(0.9-1.1), preferably 1:1.

[0015] Furthermore, the aldehyde amine condensation polymerization reaction time is 6h to 14h.

[0016] Furthermore, the temperature of the aldehyde-amine condensation polymerization reaction is 20°C to 35°C.

[0017] Furthermore, after the aldehyde-amine condensation polymerization reaction is completed, a yellow precipitate is generated in the solution, and the yellow precipitate is filtered, washed, and vacuum dried to obtain a Schiff base corrosion inhibitor.

[0018] In a third aspect, the present invention also provides a use of any of the above-mentioned Schiff base corrosion inhibitors in slowing down the corrosion of carbon steel, for example, in 1 mol·L -1 The HCl solution significantly slowed down the corrosion of carbon steel.

[0019] Compared with the prior art, the present invention has the following beneficial effects:

[0020] (1) The present invention provides a Schiff base corrosion inhibitor and a preparation method and application thereof. A Schiff base corrosion inhibitor with a planar structure is prepared by condensation polymerization of p-phenylenediamine and terephthalaldehyde. The Schiff base corrosion inhibitor is a Schiff base conjugated polymer with a degree of polymerization of 20 to 50 and a molecular weight of 3500 to 9000. The Schiff base conjugated polymer contains a large number of imine groups, which can form a larger conjugated surface structure, thereby enhancing the interaction between the Schiff base conjugated polymer and the carbon steel surface, thereby having excellent corrosion inhibition performance. -1 HCl solution can significantly slow down the corrosion of carbon steel.

[0021] (2) The preparation method of the Schiff base corrosion inhibitor provided by the present invention has a simple process and few side reactions. The yield of the Schiff base corrosion inhibitor prepared by the preparation method is high and can reach 85%.

[0022] (3) The Schiff base corrosion inhibitor provided by the present invention has a low corrosion rate at a relatively low concentration (e.g., 40 mg / L) for 1 mol·L -1 The carbon steel in HCl solution showed excellent corrosion inhibition effect, and the corrosion inhibition rate could reach 90.04%. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1are infrared spectra of p-phenylenediamine, terephthalaldehyde and Schiff base corrosion inhibitor in Example 2 of the present invention, wherein (a) is the infrared spectrum of p-phenylenediamine, (b) is the infrared spectrum of terephthalaldehyde, and (c) is the infrared spectrum of the Schiff base corrosion inhibitor;

[0024] Figure 2 At 25°C, carbon steel was treated with 1 mol·L Schiff base inhibitor (prepared in Example 2 of the present invention) at different concentrations. -1 Electrochemical impedance spectroscopy after immersion in HCl solution for 6 h, where (a) is the Nyquist curve, (bc) is the Bode diagram, and (de) is the equivalent circuit diagram;

[0025] Figure 3 At 25°C, carbon steel was treated with 1 mol·L Schiff base inhibitor (prepared in Example 2 of the present invention) at different concentrations. -1 Polarization curve after immersion in HCl solution for 6 hours;

[0026] Figure 4 The scanning electron micrographs of carbon steel surfaces after different treatments at 25°C, where (a) is a scanning electron micrograph of the carbon steel surface after sandpaper polishing, and (b) is a scanning electron micrograph of the carbon steel surface after 1 mol·L -1 Scanning electron micrograph of the surface of carbon steel after immersion in HCl solution for 6.0 h. (c) is a scanning electron micrograph of the surface of carbon steel after immersion in HCl solution containing 40 mg·L -1 1 mol·L of Schiff base corrosion inhibitor (prepared in Example 2 of the present invention) -1 Scanning electron micrograph of the surface after immersion in HCl solution for 6.0 h. DETAILED DESCRIPTION

[0027] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. This embodiment is implemented based on the technical solution of the present invention, and provides a detailed implementation method and specific operation process, but the protection scope of the present invention is not limited to the following embodiments.

[0028] Unless otherwise specified, the reagents, methods, instruments and equipment used in the present invention are conventional reagents, methods, instruments and equipment in the art. Unless otherwise specified, the reagents and materials used in the following examples are commercially available.

[0029] The present invention provides a Schiff base corrosion inhibitor, which is a polymer with a molecular weight of 3500 to 9000 and a degree of polymerization (n-1) of 20 to 50. The structural formula is as follows:

[0030]

[0031] The above-mentioned Schiff base corrosion inhibitor is prepared by the following method:

[0032] First, p-phenylenediamine is dissolved in N,N-dimethylformamide, and after stirring evenly, terephthalaldehyde is dissolved in a mixed solution of p-phenylenediamine and N,N-dimethylformamide, and stirring is continued to fully mix p-phenylenediamine and terephthalaldehyde to cause an aldehyde-amine condensation polymerization reaction; the molar ratio of p-phenylenediamine to terephthalaldehyde is 1: (0.9-1.1), preferably 1: 1; the time of the aldehyde-amine condensation polymerization reaction is 6h-14h; the temperature of the aldehyde-amine condensation polymerization reaction is 20℃-35℃. After the aldehyde-amine condensation polymerization reaction is completed, a yellow precipitate is generated in the solution, and the yellow precipitate is filtered, washed, and vacuum dried to obtain a Schiff base corrosion inhibitor.

[0033] The obtained Schiff base corrosion inhibitor can be used to slow down the corrosion of carbon steel. -1 The carbon steel in HCl solution showed excellent corrosion inhibition effect, and the corrosion inhibition rate could reach 90%.

[0034] Example 1

[0035] This embodiment first provides a method for preparing a Schiff base corrosion inhibitor, which is as follows:

[0036] ① Weigh 1.08g of analytically pure p-phenylenediamine and place it in a beaker. Add 30mL of N,N-dimethylformamide and stir evenly to fully dissolve it. Then weigh 1.34g of analytically pure terephthalaldehyde and add it to the above solution. Stir evenly to fully dissolve it.

[0037] ② Place the N,N-dimethylformamide solution containing p-phenylenediamine and terephthalaldehyde on a magnetic stirrer and stir at room temperature for 8 hours;

[0038] ③ After filtering the solution obtained in step ②, a large amount of golden precipitate was obtained. After washing with anhydrous ethanol for 3 times, the filter cake was taken out and vacuum dried at 60° C. for 24 hours to obtain a paraphenylenediamine-conjugated terephthalaldehyde Schiff base conjugated polymer corrosion inhibitor with a yield of about 50%.

[0039] The aldehyde content in the Schiff base conjugated polymer corrosion inhibitor molecule was measured at room temperature using the hydroxylamine hydrochloride titration method, and then the molecular weight of the polymer was obtained. The calculation steps are as follows:

[0040] (1) Calculate the consumed hydroxylamine:

[0041] The volume of hydroxylamine hydrochloride consumed was recorded, and the number of moles of hydroxylamine hydrochloride consumed was calculated from its concentration based on the following formula:

[0042] n 盐酸羟胺 =V 盐酸羟胺 ·C 盐酸羟胺 ;

[0043] Where n 盐酸羟胺is the number of moles of hydroxylamine hydrochloride, V 盐酸羟胺 is the volume of hydroxylamine hydrochloride consumed, C 盐酸羟胺 is the concentration of hydroxylamine hydrochloride.

[0044] (2) Calculate the number of moles of aldehyde groups:

[0045] Assuming that each aldehyde group reacts with one hydroxylamine molecule, the number of moles of aldehyde groups equals the number of moles of hydroxylamine hydrochloride consumed.

[0046] (3) Calculate the molecular weight of the Schiff base conjugated polymer based on the following formula:

[0047]

[0048] Where M is the molecular weight of the Schiff base conjugated polymer, m is the mass of the Schiff base polymer in the solution (g), and n is 盐酸羟胺 is the number of moles of hydroxylamine hydrochloride.

[0049] The molecular weight of the Schiff base conjugated polymer corrosion inhibitor of this example was measured to be 4420, and the degree of polymerization was 25.

[0050] Then, the corrosion inhibition performance of the Schiff base corrosion inhibitor sample prepared in this embodiment on carbon steel was evaluated by an electrochemical test method, and the steps were as follows:

[0051] Carbon steel pretreatment: Polish the carbon steel samples with sandpaper of different roughness (60#~1500#). After polishing, clean the samples with acetone and vacuum dry them for later use.

[0052] Weigh 60 mg of the prepared Schiff base corrosion inhibitor and add it to 1 L of 1 mol·L -1 HCl solution, and then the corrosion of carbon steel after immersion in the HCl solution for 6 hours was measured. The corrosion inhibition performance of the Schiff base corrosion inhibitor sample of this embodiment on carbon steel was evaluated by electrochemical testing method.

[0053] Electrochemical tests were performed in a three-electrode system at room temperature (25°C) on a CHI660e electrochemical workstation with a carbon steel electrode as the working electrode (exposed surface area 1 cm 2 ), using a saturated calomel electrode as the reference electrode and a platinum sheet as the auxiliary electrode, the electrochemical impedance spectroscopy of the sample was measured. The open circuit potential test time was 400s, and the electrochemical impedance measurement frequency was 10 5 ~10 -2 Hz, amplitude 10mV. The polarization curve of carbon steel electrode is measured by scanning the electrode potential in the open circuit potential range of ±300mV, with a scanning rate of 1mV, and the measurement is completed from low to high.

[0054] The electrochemical test results show that when the corrosion inhibitor concentration is 60 mg·L -1When the Schiff base corrosion inhibitor sample of this embodiment is 1 mol·L -1 The corrosion inhibition rate of carbon steel in HCl solution can reach 80%.

[0055] Example 2

[0056] This embodiment first provides a method for preparing a Schiff base corrosion inhibitor, which is as follows:

[0057] ① Weigh 1.08g of analytically pure p-phenylenediamine and place it in a beaker. Add 30mL of N,N-dimethylformamide and stir evenly to fully dissolve it. Then weigh 1.34g of analytically pure terephthalaldehyde and add it to the above solution. Stir evenly to fully dissolve it.

[0058] ② Place the N,N-dimethylformamide solution containing p-phenylenediamine and terephthalaldehyde on a magnetic stirrer and stir at room temperature for 12 hours;

[0059] ③ After filtering the solution obtained in step ②, a large amount of golden precipitate was obtained. After washing with anhydrous ethanol for 3 times, the filter cake was taken out and vacuum dried at 60° C. for 24 hours to obtain a paraphenylenediamine-conjugated terephthalaldehyde Schiff base conjugated polymer corrosion inhibitor with a yield of about 85%.

[0060] The aldehyde content in the Schiff base conjugated polymer corrosion inhibitor molecule was measured at room temperature using the hydroxylamine hydrochloride titration method, and then the molecular weight of the polymer was obtained. The calculation steps are as follows:

[0061] (1) Calculate the consumed hydroxylamine:

[0062] The volume of hydroxylamine hydrochloride consumed was recorded, and the number of moles of hydroxylamine hydrochloride consumed was calculated from its concentration based on the following formula:

[0063] n 盐酸羟胺 =V 盐酸羟胺 ·C 盐酸羟胺 ;

[0064] Where n 盐酸羟胺 is the number of moles of hydroxylamine hydrochloride, V 盐酸羟胺 is the volume of hydroxylamine hydrochloride consumed, C 盐酸羟胺 is the concentration of hydroxylamine hydrochloride.

[0065] (2) Calculate the number of moles of aldehyde groups:

[0066] Assuming that each aldehyde group reacts with one hydroxylamine molecule, the number of moles of aldehyde groups equals the number of moles of hydroxylamine hydrochloride consumed.

[0067] (3) Calculate the molecular weight of the Schiff base conjugated polymer based on the following formula:

[0068]

[0069] Where M is the molecular weight of the Schiff base conjugated polymer, m is the mass of the Schiff base polymer in the solution (g), and n is 盐酸羟胺 is the number of moles of hydroxylamine hydrochloride.

[0070] The molecular weight of the Schiff base conjugated polymer corrosion inhibitor of this embodiment was measured to be 8445, and the degree of polymerization was 48.

[0071] The Schiff base corrosion inhibitor prepared in this example was tested as follows:

[0072] (1) Infrared characterization

[0073] The infrared spectra of the p-phenylenediamine, p-terephthalaldehyde and the prepared Schiff base corrosion inhibitor of this example were measured by Fourier transform infrared spectrometer through attenuated total reflection method. The results are as follows: Figure 1 As shown, (a) is the infrared spectrum of p-phenylenediamine, (b) is the infrared spectrum of terephthalaldehyde, and (c) is the infrared spectrum of Schiff base corrosion inhibitor (PPTE): 1696 cm -1 is the carbonyl (C=O) absorption peak, 1611cm -1 The absorption peak of imine group (-C=N)- is 1493cm -1 , 1367cm -1 and 1297cm -1 It is the absorption peak of benzene ring skeleton vibration, 845cm -1 The peak at indicates disubstitution of the benzene ring.

[0074] (2) Characterization of corrosion inhibition performance (electrochemical test)

[0075] Carbon steel pretreatment: Polish the carbon steel samples with sandpaper of different roughness (60#~1500#). After polishing, clean the samples with acetone and vacuum dry them for later use.

[0076] Containing different concentrations (20mg·L -1 , 40mg·L -1 、60mg·L -1 、80mg·L -1 、100mg·L -1 ) of Schiff base corrosion inhibitor 1mol·L -1 Preparation of HCl solution: 20 mg, 40 mg, 60 mg, 80 mg and 100 mg of the Schiff base corrosion inhibitor prepared in this example were weighed and added to 1 L of 1 mol·L -1 HCl solution to obtain 1 mol·L -1 HCl solution. Then, the corrosion of carbon steel immersed in the above HCl solution was measured. The corrosion inhibition performance of the Schiff base corrosion inhibitor sample on carbon steel was evaluated by electrochemical testing method.

[0077] Electrochemical tests were performed in a three-electrode system at room temperature (25°C) on a CHI660e electrochemical workstation with a carbon steel electrode as the working electrode (exposed surface area 1 cm 2 ), using a saturated calomel electrode as the reference electrode and a platinum sheet as the auxiliary electrode, the electrochemical impedance spectroscopy of the sample was measured. The open circuit potential test time was 400s, and the electrochemical impedance measurement frequency was 10 5 ~10 -2 Hz, amplitude 10mV. The polarization curve of carbon steel electrode is measured by scanning the electrode potential in the open circuit potential range of ±300mV, with a scanning rate of 1mV, and the measurement is completed from low to high.

[0078] The electrochemical test results are as follows Figure 2 , Figure 3 shown.

[0079] Figure 2 At 25℃, carbon steel was exposed to 1 mol·L Schiff base corrosion inhibitor with different concentrations. -1 Electrochemical impedance spectroscopy after immersion in HCl solution for 6 hours, where (a) is the Nyquist curve, (bc) is the Bode diagram, and (de) is the equivalent circuit diagram. Figure 2 As can be seen from (a), with the increase of the concentration of corrosion inhibitor, the polarization resistance R p The larger the corrosion inhibitor concentration is, the -1 When the polarization resistance R p The value reaches the maximum, and the corrosion inhibition effect is the best; then with the increase of corrosion inhibition concentration, the polarization resistance R p The value begins to decrease, and the corrosion inhibition effect becomes worse. From the Bode diagram ( Figure 2 (b)) It can be seen that as the concentration of the added corrosion inhibitor increases, the impedance modulus also increases, but the shape of the curve remains basically unchanged; Figure 2 (c) It can be seen that the corrosion inhibitor concentration is 40 mg·L -1 When , the phase angle offset is the largest. According to the equivalent circuit ( Figure 2 The fitted data are shown in Table 1.

[0080] Table 1 At 298K, low carbon steel without and with different concentrations of corrosion inhibitors 1 mol·L -1 EIS data after 6 hours of immersion in HCl solution after equivalent circuit fitting

[0081]

[0082] As shown in Table 1, the equivalent circuit consists of the double layer capacitance (Q), polarization resistance (R p ), solution resistance (Rs )、Inhibitor film resistance (R dl ) and calculate the relevant dispersion effect coefficient (n). When the inhibitor concentration is 40 mg·L -1 When the polarization resistance R p The maximum value, corrosion inhibition efficiency η EIS (The calculation formula is as follows) The maximum is 90.04%.

[0083] Corrosion inhibition efficiency η EIS Calculation formula:

[0084]

[0085] Among them, R p 0 and R p Represent the polarization resistance without and with Schiff base corrosion inhibitor, respectively.

[0086] Figure 3 At 25℃, carbon steel was exposed to 1 mol·L Schiff base inhibitors at different concentrations. -1 Polarization curve after immersion in HCl solution for 6 hours. Figure 3 It can be seen that the shapes of the anodic and cathodic curves are basically the same, indicating that the addition of the corrosion inhibitor does not affect the corrosion rate of low carbon steel at 1 mol·L -1 Corrosion mechanism in HCl solution.

[0087] Figure 3 The fitting data of the polarization curves are shown in Table 2.

[0088] Table 2 At 298K, low carbon steel without and with different concentrations of corrosion inhibitor 1 mol·L -1 Polarization curve fitting data in HCl solution

[0089]

[0090] As shown in Table 2, the corrosion inhibitor concentration increases by 20 mg·L -1 , E corr The maximum displacement is about 30mV. The Schiff base corrosion inhibitor studied is a mixed corrosion inhibitor. In addition, the corrosion inhibition efficiency η calculated by the corrosion current PDP It can be concluded that the corrosion inhibition efficiency increases with the increase of the corrosion inhibitor concentration. When the corrosion inhibitor concentration is 40 mg·L -1 When the corrosion inhibition efficiency η PDP (The calculation formula is as follows) It reaches a maximum of 89.62% and then gradually decreases.

[0091] Corrosion inhibition efficiency η PDP Calculation formula:

[0092]

[0093] Among them, i corr * and i corr Represent the corrosion current density with and without corrosion inhibitor, respectively.

[0094] (3) Scanning electron microscopy characterization

[0095] Scanning electron microscopy was used to evaluate the corrosion inhibition performance of Schiff base inhibitor samples on carbon steel.

[0096] Carbon steel pretreatment: Polish the carbon steel samples with sandpaper of different roughness (60#~1500#). After polishing, clean the samples with acetone and vacuum dry them for later use.

[0097] The freshly polished carbon steel and the -1 Carbon steel immersed in HCl solution for 6 hours and in 40 mg·L -1 1mol·L of corrosion inhibitor -1 After being immersed in the HCl solution for 6 hours, the carbon steel was rinsed with deionized water, dried, and then photographed using a scanning electron microscope. Figure 4 shown. Figure 4 The scanning electron micrographs of the carbon steel surface after different treatments at 25°C, where (a) is the scanning electron micrograph of the carbon steel surface after sandpaper polishing, and (b) is the scanning electron micrograph of the carbon steel surface after 1 mol·L -1 Scanning electron micrograph of the surface of carbon steel after immersion in HCl solution for 6.0 h. (c) is a scanning electron micrograph of the surface of carbon steel after immersion in HCl solution containing 40 mg·L -1 1 mol·L of Schiff base corrosion inhibitor -1 Scanning electron micrograph of the surface after immersion in HCl solution for 6.0 h.

[0098] Figure 4 Shown: SEM image of a freshly polished carbon steel surface before immersion ( Figure 4 (a) shows that the carbon steel surface is smooth and not corroded; at 1 mol·L -1 After immersion in HCl solution, in the absence of Schiff base corrosion inhibitor, the carbon steel surface was severely corroded, with pits and more corrosion products on the sample surface ( Figure 4 (b)), indicating that the corrosion of the solution caused serious damage to the metal surface; -1 Add 40 mg·L HCl solution -1 After adding Schiff base corrosion inhibitor, the surface of carbon steel samples became smoother and denser ( Figure 4 (c) ) There are almost no obvious cracks and pits, indicating that the metal is protected from strong corrosion by the acidic solution.

[0099] The above results show that the Schiff base corrosion inhibitor prepared in this example has a -1 It has excellent corrosion inhibition effect on carbon steel in HCl solution.

[0100] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.

Claims

1. A Schiff base corrosion inhibitor, characterized in that: The Schiff base corrosion inhibitor is a polymer with a molecular weight of 3500 to 9000 and a structural formula as follows:

2. A Schiff base corrosion inhibitor according to claim 1, characterized in that: The polymerization degree (n-1) of the Schiff base corrosion inhibitor is 20-50.

3. A method for preparing a Schiff base corrosion inhibitor as claimed in claim 1 or 2, characterized in that: The method comprises the following steps: an aldehyde-amine condensation polymerization reaction is carried out on p-phenylenediamine and p-terephthalaldehyde to obtain the Schiff base corrosion inhibitor.

4. The method for preparing a Schiff base corrosion inhibitor according to claim 3, characterized in that: Dissolve p-phenylenediamine and terephthalaldehyde in N,N-dimethylformamide to undergo aldehyde-amine condensation polymerization.

5. The method for preparing a Schiff base corrosion inhibitor according to claim 4, characterized in that: First, p-phenylenediamine is dissolved in N,N-dimethylformamide, and after stirring evenly, terephthalaldehyde is dissolved in the mixed solution of p-phenylenediamine and N,N-dimethylformamide, and stirring is continued to fully mix p-phenylenediamine and terephthalaldehyde to cause aldehyde-amine condensation polymerization reaction.

6. The method for preparing a Schiff base corrosion inhibitor according to claim 3, characterized in that: The molar ratio of p-phenylenediamine to terephthalaldehyde is 1:(0.9-1.1).

7. The method for preparing a Schiff base corrosion inhibitor according to claim 3, characterized in that: The reaction time of the aldehyde-amine condensation polymerization is 6h to 14h.

8. The method for preparing a Schiff base corrosion inhibitor according to claim 3, characterized in that: The temperature of the aldehyde amine condensation polymerization reaction is 20°C to 35°C.

9. The method for preparing a Schiff base corrosion inhibitor according to claim 3, characterized in that: After the aldehyde-amine condensation polymerization reaction is completed, a yellow precipitate is generated in the solution. The yellow precipitate is filtered, washed, and vacuum dried to obtain a Schiff base corrosion inhibitor.

10. Use of the Schiff base corrosion inhibitor according to claim 1 or 2 in slowing down the corrosion of carbon steel.

Citation Information

Patent Citations

  • Composite electroactive materials for charge storage devices

    WO2018162890A1